Effect of Temperature and Naproxen Sodium Over the Micellization Behaviour of N-Cetyl N,N,N-trimethyl ammonium bromide - Fatima Durrani, Gulrez; Kaleem Baloch, Musa; Saeed Khattak, Noor; Niazi, Ayesha; Irfan Ullah, Mohd.; Rauf, Abdur (Asian Journal of Chemistry, 2013)
Critical micelle concentration of N-cetyl N,N,N-trimethyl ammonium bromide (CTAB) and its mixture with drug naproxen sodium were determined at different temperature by using surface tension technique. Naproxen sodium, a non-steroidal anti-inflammatory drug, which has been found to exhibit typical amphiphilic behaviour in aqueous solution in that they accumulate at interface, depressing the surface tension and form aggregate in solution at sufficiently high concentration. So critical micelle concentration of N-cetyl N,N,N-trimethyl ammonium bromide decreased as the concentration of drug increases and same is the case with temperature. Thermodynamic parameters like DGmic, DHmic and DSmic of micellization of N-cetyl N,N,Ntrimethyl ammonium bromide were also determined in the presence of naproxen sodium salt at different temperature, which shows that free energy of micellization, is favoured in the presence of drug and become more favourable with the temperature.